K‐Oxyma: a Strong Acylation‐Promoting, 2‐CTC Resin‐Friendly Coupling Additive. Issue 28 (23rd August 2013) - Cherkupally, Prabhakar; Acosta, Gerardo A.; Nieto‐Rodriguez, Lidia; Spengler, Jan; Rodriguez, Hortensia; Khattab, Sherine N.; El‐Faham, Ayman; Shamis, Marina; Luxembourg, Yoav; Prohens, Rafel; Subiros‐Funosas, Ramon; Albericio, Fernando
Abstract: Here we present a new formulation of the recently introduced OxymaPure additive for peptide bond formation, in which the N ‐hydroxylamine group is replaced by a potassium salt. The complete suppression of its acidity converts K‐Oxyma into the most suitable coupling choice when peptides are assembled on highly acid‐labile solid‐supports. The coupling efficiency and diminished prospects for epimerization are conserved relative to OxymaPure. In addition, K‐Oxyma displays excellent solubility in a variety of organic solvents and undergoes safer decomposition than classical 1‐hydroxybenzotriazole additives. Abstract : A new oxime‐based coupling additive is introduced for peptide bond formation. The potassium salt of OxymaPure, K‐Oxyma, is readily obtained from commercially available precursors. Unlike common N ‐hydroxylamines, K‐Oxyma is compatible with extremely acid‐labile solid‐supports, displays excellent solubility, minimizes epimerization, and enhances coupling efficiency relative to OxymaPure.